2007
DOI: 10.1002/dvdy.21098
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles for zic genes in early development

Abstract: Members of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
129
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(138 citation statements)
references
References 151 publications
(225 reference statements)
8
129
1
Order By: Relevance
“…Previous studies reported that SUFU is able to stabilize Gli2 and Gli3 against proteasomal degradation by antagonizing their interaction with SPOP/Cul3 (30,32). However, we were unable to observe any effects of SPOP on Glis3, 3 suggesting that another BTB domain-containing protein may mediate the interaction between Glis3 and Cul3. In addition to an effect on protein stability, SUFU was shown to inhibit the transcriptional activity of Glis3.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Previous studies reported that SUFU is able to stabilize Gli2 and Gli3 against proteasomal degradation by antagonizing their interaction with SPOP/Cul3 (30,32). However, we were unable to observe any effects of SPOP on Glis3, 3 suggesting that another BTB domain-containing protein may mediate the interaction between Glis3 and Cul3. In addition to an effect on protein stability, SUFU was shown to inhibit the transcriptional activity of Glis3.…”
Section: Discussioncontrasting
confidence: 80%
“…Gli-similar 1-3 (Glis1-3) 2 constitute a distinct subfamily of Krüppel-like zinc finger transcription factors that are related to members of the Gli family and the Drosophila homolog Cubitus interruptus (Ci), the downstream effectors of Hedgehog signaling, and proteins in the Zic family (1)(2)(3). Homology among Glis, Zic, and Ci/Gli proteins is limited to the five Cys 2 -His 2 zinc finger motifs shared by all three subfamilies, with little or no similarity outside of the region (4).…”
mentioning
confidence: 99%
“…Expression in the presumptive cerebral-ganglion-forming cells seems to be homologous to the expression of the Zic homologues in the earliest neuroectoderm. Ttu-Zic expression in the earliest mesodermal cells may be consistent with that in vertebrates and ascidians (references in Merzdorf 2007). Most interestingly, the Ttu-Zic expression pattern in the segmented mesodermal cell lineage is very similar to the differentiation-stage-specific expression changes in Zic1, Zic2, and Zic3 that are observed in the course of mammalian somitogenesis (Inoue et al 2007): Zic3 is detected in the earliest mesodermal cells adjacent to the primitive streaks, the Zic2 expression is enhanced in forming somites and most newly formed somites, and the expression of the three Zic genes continues in the dorsomedial part of the somite derivatives in later embryonic development.…”
Section: Expression Of Zic In Cerebral-ganglion-forming Regionsupporting
confidence: 61%
“…Expression and functional analyses indicate that Zic zinc finger proteins commonly play roles in cell differentiation and proliferation in the early embryonic stages in Deuterostomia, Ecdysozoa, and Cnidaria (reviewed in Aruga 2004;Merzdorf 2007). However, an obvious defect in our understanding of the Zic phylogeny is the lack of information on lophotrochozoan Zic in the literature, except in terms of gene structure.…”
Section: Introductionmentioning
confidence: 99%
“…27 Indeed, heterozygous deletions of the adjacent ZIC1 (MIM 600470) and ZIC4 (MIM 608948) genes cause Dandy-Walker malformation (MIM 220200), the most common human congenital cerebellar malformation, 27 and deletion of Zic1 in mouse results in cerebellar malformations and axial skeletal abnormalities. 28 Zic genes have critical roles in various developmental processes and are regulated by a number of pathways/TFs. We postulate that ZNF592 might be a downstream or upstream element in the Zic-regulated pathways.…”
Section: Resultsmentioning
confidence: 99%